Testing-Related Health Impact of Transrectal and Transperineal Prostate Biopsy as Assessed by Health Utilities. Issue 6 (21st December 2021) - Shankar, Prasad R.; Ellimoottil, Chad; George, Arvin K.; Hadj-Moussa, Miriam; Modi, Parth K.; Salami, Simpa; Tosoian, Jeffrey J.; Wei, John T.; Davenport, Matthew S.
Abstract : Purpose: We sought to assess the temporary health-related quality of life (health utility) of nonmagnetic resonance imaging-guided transrectal and transperineal prostate biopsy. Materials and Methods: This is a 2-arm, prospectively enrolled, observational, patient-reported outcomes study, performed between June 2019 and November 2020 at a single academic medical center. Inclusion criteria were men undergoing an outpatient ultrasound-guided prostate biopsy (transrectal or transperineal approach, without magnetic resonance imaging guidance). Patients with a history of Gleason 7+ prostate cancer were excluded. Validated survey instruments were utilized to assess baseline (Short Form 12) and testing-related (Testing Morbidities Index [TMI]) health utility states. The primary outcome was the TMI summary testing-related quality-of-life score (summary utility score; scale: 0=death and 1=perfect health). The TMI is comprised of 7 domains, spanning before, during and after testing experiences. Each domain is scored from 1 (no health impact) to 5 (extreme health impact). Testing-related quality-of-life measures were compared with Mann-Whitney U test. Results: Enrollment rates were 80% (60/75; transrectal) and 86% (60/70; transperineal). All patients (120/120) completed the questionnaire. The TMI summary score for transrectal biopsy was not significantly different from transperineal biopsy (0.86, 95% CI 0.84–0.88 vs 0.83, 95% CI 0.81–0.85; p=0.0774). The largest difference in the testing experiences was related to intraprocedural pain (transrectal biopsy: 2.3, 95% CI 2.1–2.4; transperineal biopsy: 2.9, 95% CI 2.6–3.1; p <0.001). Conclusions: Transperineal and transrectal prostate biopsies have similar effect on temporary health-related quality-of-life. Transient differences relate to intraprocedural pain. These data can inform clinical decision making and future cost-utility models.